2003
DOI: 10.1002/app.13408
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of wood reacted with a phosphorus pentoxide–amine system

Abstract: ABSTRACT:The objective of this research was to improve the fire-retardant properties of wood in one treatment using a phosphorus pentoxide-amine system. Phosphorus pentoxide and 16 amines including alkyl, halophenyl, and phenyl amines were compounded in N,N-dimethylformamide and the resulting solutions containing phosphoramides were reacted with wood. The characteristics of phosphoramidereacted wood were analyzed by FTIR, energy-dispersive X-ray analysis, and elemental analysis. Fire retardancy of phosphoramid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Thermal degradation of lignocellulosic materials begins with an early decomposition of hemicelluloses, followed by an early stage of pyrolysis of lignin, depolymerization of cellulose, active flaming combustion and char oxidation (Lee et al 2004). The TGA curves of the EFB fibers before and after treatments are shown in Fig.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Thermal degradation of lignocellulosic materials begins with an early decomposition of hemicelluloses, followed by an early stage of pyrolysis of lignin, depolymerization of cellulose, active flaming combustion and char oxidation (Lee et al 2004). The TGA curves of the EFB fibers before and after treatments are shown in Fig.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…( Lee et al 2004) showed that phosphoramides, when bonded to cellulose, increase the char yield and lower the weight loss rates in comparison to phosphorus pentoxide and amine treated wood used as comparisons.…”
Section: Phosphorus/nitrogen Synergismmentioning
confidence: 99%
“…Generally, the degradation of wood is caused by light irradiation or by heat treatment [17,21,22]. Thermal degradation of wood is highly dependent on its constituents [17,23,24].…”
Section: Introductionmentioning
confidence: 99%